MUDRA Scheme – A Boon to MSME Financing - S, Dr. Nisa (Journal of Business Management and Economics, 2018)
Micro, Small and Medium Enterprises (MSME) play a dominant role in Indian economy by contributing to rise in national income, creating employment opportunities, nurturing the talent among the young entrepreneurs, making available supply of mass consumption goods etc. However, the sector faces severe problems and the most important of them is the inadequate access to finance. Even though the priority of the policy makers and practitioners has been to step up the access and availability and credit to micro and small and enterprise sector, one reason or other, the sector continues to suffer. Reserve Bank of India, in collaboration with ministry of micro, small and medium enterprises has been quite positive in introducing various measures so that the credit off take to the sector improves. The recent innovation in this regard is introduction and implementation of MUDRA Scheme (Micro Units Development and Rehabilitation Agency) by Govt. of India. The objective of the paper is to look into the objectives of setting up MUDRA Scheme and trace out how it has made an impact among the MSME sector in answering to the questions of access and availability of credit to the sector. To get an insight of the study, field level implementation of MUDRA Scheme in certain districts of Kerala has been taken. Primary data has been collected from credit institutions participating in the scheme. Literature review has been resorted gather the significance of the scheme with particular focus to the development of the sector. The study is significant to reiterate the advocacy of such innovative schemes for the promotion of the sector so that small entrepreneurs get relieved from their problem of access to finance.